(untitled) (Revista de Artes Marciales Asiáticas, 2014)
There are more than twenty different traditional wrestling arts that are practiced in today Iran. One of them which is practiced in the region of great Khorasan province is called kosti-ye ba cuxe (ba cuxe wrestling). This wrestling art is performed by wearing knee-length pants and a thick jacket and is famed for its powerful throws and leg trips. The following article deals with the history of ba cuxe wrestling and its fundamental techniques. First an introduction to this type of wrestling is given. Later the article describes the background and the regions of practice of ba cuxe wrestling. In the next section the rules and regulation of ba cuxe matches are provided. Then, based on the available literature on the topic and also on fieldwork, the article expands on the fundamental techniques in this traditional wrestling style.